(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The article analyzes the general tendencies of Cuban historiography referent to the different discussions that the first Cuban presidential election provoked in the historical memory at the end of the twentieth century. We consider that there are two main elements that are involved in the explanation of the meaning and the implications of the mentioned presidential election and the establishment of the republic. In may 1902, from which the Cuban historiography dedicates the topic. One refers to the hegemonic condition, the expansionist impulse and the American interest in the island. The other aspect focuses on the efforts of the social and Cuban politicians’ factors to obtain the independence and take the first steps in building their national identity. The historiography journey does not attempt to give an exhaustive bibliographic list, but in supplying a balance about the main ideological and political influences of the press notes carried out in Cuba around the Republic coming.